Factores de riesgo para tuberculosis pulmonar en personal sanitario del Hospital Regional Docente de Trujillo durante el periodo 2007-2017 - Loredo Torres, Jorge Antonio (2019)
Pulmonary tuberculosis is generally associated with conditions of poverty and overcrowding, with easy capacity for transmission by respiratory route and that can present as active disease or in a latent form. The latter is the most risky because a person infected with the tubercle bacillus can infect without even manifesting the active disease by taking the patient to health facilities for consultations due to respiratory or other symptoms. That is why the transmission of pulmonary tuberculosis constitutes an important occupational risk in hospitals where a large number of patients are received daily either diagnosed, underdiagnosed or with inadequate treatment, being the direct contact with health personnel the most important risk factor for their Intrahospital transmission in emergency services and outpatient services. There are few studies in Peru that attempt to describe which are the main risk factors for the transmission of pulmonary tuberculosis in health personnel, this is why the present work seeks to identify these factors within the health staff of the Regional Teaching Hospital of Trujillo during a period of 10 years, thereby contributing to their recognition to reduce the in-hospital infectivity rate.